Women's human rights and Tunisian upheavals: is 'democracy' enough?. Issue 3 (2nd July 2016) - Winter, Bronwyn
ABSTRACT: The regimes that came to power (in some cases ephemerally) in the wake of the so-called 'Arab spring' claimed democratic legitimacy as a primary means of credentialling their political agenda in international and even local eyes. Yet, how legitimate some of these new regimes have been is open to question. So-called 'moderate' Islamist movements have been criticised as using democratic processes to introduce new forms of theocratic authoritarianism and/or for not paying sufficient attention to strengthening and resourcing the political, legal and civic institutions, which make democracy effective. Moreover, women's rights have been under fire in both overt and covert ways. Through a study of Tunisia, touted as one of the success stories – indeed the only one for the moment – of the 'Arab spring', this article investigates the question of 'democratic legitimacy' from a feminist perspective.